Initial infrastructure for knowledge grid model to facilitate knowledge sharing in big data environment - Hosseinioun, Sara; Abdullah, Rusli; A. Jabar, Marzanah; Jusoh, Yusmadi Yah (School of Computing, College of Arts and Sciences, Universiti Utara Malaysia, 2018)
Recently, the improvement of computer processing ability, storage capacity and, communication drive business and organizations to improve their resources by using big data, also they gathered by their interest as a community to share their knowledge and skills to develop vision and strategies. Knowledge grid designed to deal with a large number of data sets in grids for efficient capture, publish, share, and manage knowledge resources. This study discovered the relation between knowledge grid and big data and its impact on knowledge sharing. Also listed the factors which impact knowledge sharing from several models. It concluded with the connection of knowledge grid with these factors and community member’s role in knowledge sharing among big data community.